Penggunaan Semen Portland Sebagai Bahan Pengganti Abu Batu/Filler terhadap Karakteristik Aspal AC-WC - Ma’ulva, Ade Arya; Ridwan, Ahmad; Damara, Bobby (Jurnal Talenta Sipil, 2025)
The need for high-quality road infrastructure encourages the improvement of pavement material performance, especially asphalt concrete mixtures. One of the important components in AC-WC asphalt concrete mixtures is filler, which functions to fill the voids between aggregates and increase mixture stability.This study aims to determine the effect of using Portland cement as a substitute for stone ash (filler) on the characteristics of AC-WC asphalt mixture. Tests were conducted at the Civil Engineering Laboratory of Lamongan Islamic University, using quantitative methods. Some of the parameters tested included specific gravity, ductility, softening point, flash point, and asphalt burn point, as well as Marshall testing to determine the values of stability, flow, and Marshall Quotient. This research used Portland cement filler with variations of 0%, 2%, 4%, and 5%.The results showed that the highest Marshall Properties value was found in the 5% variation with a stability value of 1472.13 kg, VMA value of 19.12%, VFA value of 80.84%, VIM value of 3.66%, flow value of 3.10 mm, and MQ value of 474.88 kg/mm. Thus, Portland cement can be used as an alternative filler in AC-WC asphalt mixtures to support better performance of the top pavement layer.